Sosialisasi Batas Area Renang Yang Aman Berdasarkan Kondisi Batimetri Kawasan Wisata Pantai Tanjung Bayang Makassar - Taufiqur Rachman (Faculty of Engineering UNHAS, 2023)
Tanjung Bayang Beach tourist area is one of the marine tourist destinations in Makassar city that is visited on weekends. Tourist activities that can be done at Tanjung Bayang Beach are swimming, riding banana boats, and fishing. However, in carrying out tourism activities on Tanjung Bayang Beach, accidents often occur due to drowning of tourists due to neglect of personal safety when swimming with extreme wave conditions. Tourism managers are still ignorant of the safety aspects of tourists in marine tourism areas such as the fulfillment of disaster signs or potential accidents that lead to disaster for tourist visitors. Socialization of safe swimming area boundaries based on bathymetric conditions of Tanjung Bayang beach tourism area has been carried out. The socialization partners are Tanjung Bayang beach tourism managers, Non-Governmental Organizations (NGO) of Tanjung Merdeka. Knowledge transfer through this socialization activity improves partners understanding of the implementation of potentially catastrophic accident management in accordance with Law of the Republic of Indonesia No. 1 of 1970 on Occupational Safety, and security and safety assurance at tourist attractions in accordance with Law of the Republic of Indonesia No. 10 of 2009 on Tourism. Socialization participants gained an increase in knowledge and understanding of the material presented by 41%.